ANALYSIS OF MEMBER SATISFACTION ON THE QUALITY OF SERVICES IN MANDIRI SHARIA COOPERATION SAVING AND LOAN UNITS - Fikri Akbar, Muhammad; Haykal, Muhammad; Sauzi Amalia, Sri; Sri Delviani, Putri; Nur Ilham, Rico (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This research aims to assess and assess member satisfaction with the services carried out by independent sharia cooperatives. Cooperatives have the goal of improving the welfare of their members. That member satisfaction with the quality of services provided by independent sharia cooperatives has a major influence in determining the improvement and development of cooperatives in achieving their goals. Techniques in data collection using literature study methods, observations, interviews, and questionnaires. Data processing techniques by collecting information, reducing, presenting, and drawing conclusions. This study used descriptive and qualitative methods with a total sample of 20 people. The sampling technique uses a questionnaire technique. Based on the results of research that has been carried out, member satisfaction with service services in cooperatives obtained high responder responses of as much as 73%, moderate responses as much as 18%, low responses as much as 10%. There are 5 variables that determine the quality of service, namely physical evidence, reliability, responsiveness, assurance, and empathy.